2022
DOI: 10.3390/v14081819
|View full text |Cite
|
Sign up to set email alerts
|

A TaqMan Probe-Based Multiplex Real-Time PCR for Simultaneous Detection of Porcine Epidemic Diarrhea Virus Subtypes G1 and G2, and Porcine Rotavirus Groups A and C

Abstract: Porcine viral diarrhea diseases affect the swine industry, resulting in significant economic losses. Porcine epidemic diarrhea virus (PEDV) genotypes G1 and G2, and groups A and C of the porcine rotavirus, are major etiological agents of severe gastroenteritis and profuse diarrhea, particularly among piglets, with mortality rates of up to 100%. Based on the high prevalence rate and frequent co-infection of PEDV, RVA, and RVC, close monitoring is necessary to avoid greater economic losses. We have developed a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…In 2022, a study conducted in Heilongjiang province reported an RVA positive rate of 4.3% (12/280) [ 25 ]. Additionally, a study conducted in Jiangsu province in 2022 reported an RVA positive rate of 12.5% (11/88) [ 26 ]. For a comprehensive understanding of the prevalence of PoRVA in China, a large number of porcine diarrheal samples were collected from the major provinces in pig production.…”
Section: Discussionmentioning
confidence: 99%
“…In 2022, a study conducted in Heilongjiang province reported an RVA positive rate of 4.3% (12/280) [ 25 ]. Additionally, a study conducted in Jiangsu province in 2022 reported an RVA positive rate of 12.5% (11/88) [ 26 ]. For a comprehensive understanding of the prevalence of PoRVA in China, a large number of porcine diarrheal samples were collected from the major provinces in pig production.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the number of porcine RVC genomes has increased significantly, indicating that it has higher genetic diversity than other host species [ 22 ]. The positive rate for PoRVC was detected using a TaqMan Probe-Based Multiplex Real-Time PCR, indicating that the prevalence rate of PoRVC had been previously underestimated [ 23 ]. To facilitate the classification of rotavirus strains, a Rotavirus Classification Working Group (RCWG) was formed to set diagnostic guidelines and propose a classification system [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…While the window for the detection of viral shedding using antigen-based detection methods is relatively short (up to one week after onset of diarrhea), viral nucleic acids can be detected for longer periods (e.g., via RT-PCR) [ 248 ]. Currently, multiplex real-time quantitative RT-PCR assays for the simultaneous detection of different agents associated with acute gastroenteritis including RVA have been widely implemented [ 249 , 250 , 251 ].…”
Section: Diagnosis and Surveillance Of Rvamentioning
confidence: 99%